Anonymous: a social movement - Knight, William (2018)
This project seeks to show that the controversial hacktivist phenomenon Anonymous might be most appropriately understood through the lens of Social Movement Theory. Based upon data gathered from four years of observation and interviews among self-identifying members of the Anonymous movement, this project is an exploration of the state of the Anonymous movement as it exists in its current form, and also a look back a the movement since its political birth in 2008. This project ultimately concludes that there are elements of social movement theories which do indeed apply to Anonymous, but there are areas in which theory might be updated to best understand such a tumultuous and dynamic movement.